METHOD FOR THE CONSTRUCTION OF STUDENTS’ SCIENTIFIC IDENTITY WITHIN ENGLISH FOR ACADEMIC PURPOSES: THE CASE OF INTERNATIONAL STUDENTS OF MASTER PROGRAMME “INFORMATION AND ELECTRICAL ENGINEERING”AT HOCHSCHULE WISMAR - Ahrens, Andreas; Zascerinska, Jelena; Melnikova, Julija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Reaching the Goals of the 2030 Agenda for Sustainable Development is facilitated by science development. In order to strengthen scientific efforts in implementing the 2030 Agenda, the number of our modern society’s members who associate themselves with scientific community has to be increased. The research question is as following: What method promotes the construction of students’ scientific identity in language education within higher engineering education? The aim of the present research is to analyse the inter-connections between scientific identity and language education underpinning empirical analysis of use of biographical methods in English for Academic Purposes within Master programme “Information and Electrical Engineering” for International students at Hochschule Wismar. Research methods include theoretical and empirical methods. Theoretical methods comprise analysis of theoretical sources and theoretical modelling. The research methodology implies the study of the meaning of the key concepts of “scientific identity”, “language education” and “biographical method”. Moreover, the study demonstrates how the key concepts are related to higher engineering education. The empirical study was carried out at Hochschule Wismar in 2018. The data reveals students’ positive evaluation of use of biographical methods in English for Academic Purposes studies. The novel contribution of the paper is the newly formulated research question.